Anesthetic Management in an Adult Patient With Costello Syndrome: A Case Report. Issue 2 (15th July 2019) - Ugata, Kei; Imamachi, Noritaka; Hashimoto, Ai; Saito, Yoji
Abstract : Costello syndrome is a rare genetic disorder characterized by mental and growth retardation and distinctive coarse facies. A significant proportion of patients with Costello syndrome have hypertrophic cardiomyopathy, papillomata, and malignant tumors. General anesthesia practice, especially airway and cardiac management, in patients with Costello syndrome may be complicated by anatomical features and cardiac abnormalities. There have been several reports on the anesthetic management of children with Costello syndrome, but few have reported on the anesthetic management of adults with Costello syndrome. In adults, careful preoperative evaluation as well as preparation for adult-onset and previously unrecognized medical conditions are key for safe anesthetic management.